Dakwah Dalam Mengatasi Kesehatan Lingkungan Hidup di Desa Bontonyeleng Kecamatan Gantarang Kabupaten Bulukumba - Basri, Musdalifa; Muliaty, Muliaty Amin; Rahma, Rahmatiah (Danudirja Setyabudi Nusantara, 2025)
The purpose of this study is to identify the forms and synergy of da'wah used to address environmental health issues in Bontonyeleng Village, Gantarang District, Bulukumba Regency. This research employs a qualitative approach with a focus on da'wah communication. The data sources for this study consist of primary and secondary data, which are analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that the forms of da'wah utilized to address environmental health in Bontonyeleng Village include tabligh (conveying religious messages), irsyad (guidance), tadbir (management), and tamkin (empowerment). This da'wah initiative is a collaborative program involving Islamic preachers (dai), the village head, the Family Welfare Empowerment group, and healthcare workers from Bontonyeleng Community Health Center (Puskesmas). The synergy in implementing this da'wah has had a positive impact on shifting community paradigms and behaviors, as seen in the reduction of domestic waste disposal into irrigation channels. Additionally, approximately 15 out of 50 households have adopted environmentally friendly practices by establishing waste bins. It is hoped that the da'wah approach in addressing environmental health issues in Bontonyeleng Village can be comprehensively applied by the residents and serve as a reference for tackling environmental health concerns in other communities.